(untitled) (Journal of Student Affairs in Africa, 2021)
Career guidance and counselling is a vaguely implemented concept in most educational institutions, governmental and non-governmental organisations. The severity of the problem and scarcity of relevant information among university students have prompted the undertaking of this study the aim of whichwas to assess career development among undergraduate students of Madda Walabu University. Crosssectional study design was employed to gather quantitative data through self-administered structured questionnaires. The participants in the study were 605 undergraduate students of Madda Walabu University who were recruited through multi-stage sampling. The analysis employed SPSS-20.0 to calculate t-test and ANOVA. The findings suggested that socio-demographic variables were important in determining the factors, levels and variances in career development. The participants’ perceived benefit of career development has shown that there is a statistically significant difference between the expected mean and the observed mean, t(604) =29.11, p<.01. However, they had only some unsatisfactory information on career development and most of them (47.4%) did not have a bright future. The result of this study showed that career development is important in understanding students’ personal values, clarifying their goals, career choice directions and job-searching skills. Because the respondents’ reported information on career development is so poor, lack of future direction and decreased performance are inevitable. It is suggested that career counselling services are seen to be highly recommendable in advancing students’ career development in many aspects.